2014
DOI: 10.5664/jcsm.3958
|View full text |Cite
|
Sign up to set email alerts
|

Complete Blood Count Alterations after Six Months of Continuous Positive Airway Pressure Treatment in Patients with Severe Obstructive Sleep Apnea

Abstract: Study Objectives: The cardiovascular complications caused by obstructive sleep apnea (OSA) decrease after continuous positive airway pressure treatment (CPAP). Mean platelet volume (MPV), platelet distribution width (PDW), and red cell distribution width (RDW) are newly recognized tools for assessing cardiovascular risk. Methods: From a selection of patients with symptoms of nocturnal snoring and/or excessive daytime sleepiness, 36 males with an apnea-hypopnea index (AHI) > 30/h and 22 age-matched normal male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 39 publications
4
39
1
1
Order By: Relevance
“…Another study by Kurt et al reported a meaningful correlation between PDW and AHI (17). Moreover in some studies, it was proposed that treatment with continuous positive airway pressure (CPAP) devices and surgical intervention significantly reduce MPV and PDW values in patients with severe OSA (10)(11)(12)24). On contrary, almost similar number of study reported no relationship between MPV and OSA, and between PDW and OSA (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study by Kurt et al reported a meaningful correlation between PDW and AHI (17). Moreover in some studies, it was proposed that treatment with continuous positive airway pressure (CPAP) devices and surgical intervention significantly reduce MPV and PDW values in patients with severe OSA (10)(11)(12)24). On contrary, almost similar number of study reported no relationship between MPV and OSA, and between PDW and OSA (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 83%
“…MPV was also reported to be correlated with disease severity and inflammation in patients with obstructive sleep apnea and therefore, it could be used as a marker to predict cardiovascular diseases in patients with OSA (6)(7)(8). Moreover continuous positive airway pressure treatment (CPAP) reported to cause a significant decrease in the MPV and PDW values in patients with OSA (10)(11)(12). On contrary, some other studies reported no relationship between MPV and OSA, and between PDW and OSA (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This improvement in PDW values with CPAP treatment is a quite reasonable result. However, regarding this issue very few publications could be found in the literature (12), and thus, we do not know the exact mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a number of studies related to MPV and OSA, only a few studies report regarding the change in PDW values after CPAP treatment (12). Sökücü et al (12) reported in a comparison of 44 patients with severe OSA and control group that MPV values were found to be higher in the severe OSA group, whereas PDW values were similar. In contrast to our study, they reported decreased MPV values and increased PDW values after 6 months of CPAP treatment in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation